(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Prof Eme E. Osim served Editor-in-Chief of Nigerian Journal of Physiological Sciences between 1999 and 2009. This tribute highlights his immense contributions to the development of the journal and academia